THE ANALYSIS TOWARDS PROFITABILITY OF COMMERCIAL BANKS IN INDONESIA (PERIOD OF 2016-2020) - Sheila Maharani Islamidinna; Suryani Sri Lestari; Moh Muslikh (Politeknik Negeri Semarang, 2022)
The research aims is to analyze the Profitability (Return on Asset) of Commercial Banks in Indonesia Period of 2016-2020 bu using Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), and Net Interest Margin (NIM) as the independent variabels. The population used are 7 Commercial Banks in Indonesia that enter the group of Commercial Banks Business Activities 4 (BUKU 4) Period of 2016 up to 2020. While the sampling was done by puposive sampling technique, using quantitive data and secondary data. In this research the model used is Multiple Linear Regression Analysis using IBM SPSS 25 Statistics. The results and discussion showed that CAR, LDR, and NIM simultaneously have significant effect towards ROA. Furthermore, CAR and NIM have a significant effect, while LDR has no significant effect towards ROA in Commercial Banks Business Activities 4 (BUKU 4). Then, Determination Coefficient Test ( Adjusted R2) obtained the result is 41.9% which showed the contribution of Independent Variables in explaining Dependent Variables, and 58.1% is effected by other variables that are not examined in this research.